1996
DOI: 10.1055/s-2008-1058639
|View full text |Cite
|
Sign up to set email alerts
|

Iatrogenic Impairment of Hearing During Surgery for Acoustic Neuroma

Abstract: The decision to attempt hearing preservation during acoustic neuroma (AN) surgery has a dramatic impact on the choice of surgical approach. The translabyrinthine route, which has been in use for many years by otoneurosurgeons, has helped to reduce the mortality and morbidity rates. According to many authors, this is the technique of choice in subjects with poor preoperative hearing function, that is, greater than 50 dB or 70 dB in pure-tone average (PTA) and/or less than 70% or 50% in speech discrimination sco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 20 publications
0
37
0
Order By: Relevance
“…More specifically, vascular changes to the internal auditory artery, such as occlusion, rupture, or vasospasm, are believed to induce postoperative hearing deficits. 17,19,79,84,88,89,122 Strauss et al 135 found that applying medical therapy to preclude such vasospasms produced preservation rates that were more than twice as high when compared with controls.…”
Section: Intraoperative Monitoring Of the Vestibulocochlear Nerve (Cnmentioning
confidence: 99%
See 4 more Smart Citations
“…More specifically, vascular changes to the internal auditory artery, such as occlusion, rupture, or vasospasm, are believed to induce postoperative hearing deficits. 17,19,79,84,88,89,122 Strauss et al 135 found that applying medical therapy to preclude such vasospasms produced preservation rates that were more than twice as high when compared with controls.…”
Section: Intraoperative Monitoring Of the Vestibulocochlear Nerve (Cnmentioning
confidence: 99%
“…Because the stimulus response must be summed and averaged to obtain a wave of sufficiently high amplitude, the tradeoff to this process is a significant time delay that can last up to several seconds to minutes. 1,18,19,49,50,83 Naturally, such a delay can negatively influence the course of surgery, as BAEPs effectively provide data that were applicable several seconds or minutes prior.…”
Section: Brainstem Auditory Evoked Potentialsmentioning
confidence: 99%
See 3 more Smart Citations